COMPARATIVE STUDY OF KNOWLEDGE, ATTITUDE AND PRACTICE OF MIDWIVES ON ISLAMIC RULES OF MATERNITY CARE IN JALINGO LOCAL GOVERNMENT AREA, OF TARABA STATE, NIGERIA. - NAWATI Yakubu Shonzenba1; Chiegil Solomon; Goodluck Azuonwu; ID. Alabere; Cynthia Danjuma; SAMBO Mohammed Abdulrazaq; Danladi Danazumi Mungeri; Azuonwu, B (Student's Journal of Health Research, 2023)
Background: Maternity care is still a mirage due to poor knowledge, attitudes, and practice of Islamic rules of maternity care, Objectives: The purpose of this study was to compare the Knowledge, Attitude, and Practice of midwives on Islamic rules of maternity care in Jalingo LGA, Taraba state, Nigeria. Methodology:   Descriptive comparative, cross-sectional survey design with multi-stage and simple random sampling techniques. The population for the dissertation consisted of all Nurses and Midwives in two hospitals and Primary Health Care Centres and a sample size of 405 Nurses/midwives. The validated questionnaire was tested for reliability and validity with Cronbach Alfa, 0.80. Results:   The mean age of respondents was  36.10(0.43) ±8.21,   Majority were married (77.5%), female (75.3%), Muslims (65.7%), Hausa (45.6%), and those with RN and BNSc certifications (30.2/23.5%). knowledge on 24-points scale scored mean = 19.24 (0.11) ± 2.19,  Attitudes on 28-points scale, mean  =18.18 (0.16) ± 2.97 and Practice on 45-points scale, mean  = 34.83 (0.10) ± 5.71. Comparing how knowledge is spread across the type of health facilities, score were mean = 16.5 (0.18) ± 2.4 and mean  = 16.7 (0.19) ± 2.5; t- -1.001, P=0.318; mean  = 15.3 (0.3) ± 3.6 for PHCCs and mean  = 15.2 (0.3) ± 3.6, t-0.124, p=0.901 and Practices, mean = 17.6 (0.5) ± 6.4 for PHCs and mean = 17.7 (0.5) ± 6.6, t-0.114, p=0.915 for PHCCs and Hospitals respectively. Conclusion: Multi-cultural, ethnoreligious practices and perceptions concerning maternity care have posed many influences on maternity care. Recommendation: It is therefore recommended that High quality/evidence-based and culturally competent care be initiated by the midwives.